Jewish Radicalism In Winnipeg, 1905-1960: Jewish Life and Times, Volume VIII - Reilly, Nolan (Labour / Le Travail, 2005)
The article reviews the book, "Jewish Radicalism in Winnipeg, 1905-1960," edited by Daniel Stone.